DIAGNOSIS OF ACUTE AND CHRONIC HEART FAILURE (World Bulletin of Public Health, 2022)
Heart failure is characterized by a change in the structure or function of the heart, leading to its inability to deliver oxygen in accordance with the need of tissues, despite normal filling pressure. In accordance with modern international recommendations, chronic heart failure (CHF) is defined as a syndrome in which a patient has typical complaints (shortness of breath, swelling of the legs, fatigue) and symptoms (increased venous jugular pressure, wheezing in the lungs, and displaced apical thrust) as a result of changes in the structure or function of the heart
Keywords: Electrical State Of The Myocardium; Symptoms And Prevention; Patients